Design and Implementation of J2EE Application Service Middleware Monitoring System of Nanning Power Supply Bureau - Yiming Wu; Yongtao Tian (Dianxin kexue)
J2EE architecture has been widely used in power information system, monitoring J2EE application service middleware is an important task in information operation and maintenance. The object of study is Tomcat, using JMX technology to achieve the core function of monitoring system. A discussion was made in detail about the design, function modules and system implementation of J2EE application services middleware monitoring system. Development results have been put into trial operation in good condition, which is an automatic and systematic successful case of power information operation and maintenance.